Peningkatan Hasil Belajar Matematika Siswa Melalui Penerapan Model Pembelajaran Discovert Learning Di Kelas X SMA Muhammadiyah Pangkajene - Magfirah, Nur; Syam , Haerul; Ramadhan , Muhammad Agung; Hapsari (Jurnal Guru Pencerah Semesta, 2024)
The purpose of this research is to find out that the application of the Discovery Learning learning model can improve student learning outcomes at Muhammadiyah Pangkajene High School for the 2022/2023 academic year. This research was a group study involving 14 class X students of SMA Muhammadiyah Pangkajene. The instrument is a test consisting of 5 questions. The results of observations on learning outcomes obtained by applying the discovery learning learning model reached 68%, namely. 8 students out of 14 completed their studies. Observation results of the second comprehensive study reached 76% namely. 11 out of 14 students complete their studies. Based on the results of cycles I and II, it was concluded that the application of the Discovery Learning learning model could improve the learning outcomes of Muhammadiyah Pangkajene High School students for the 2022/2023 academic year.